PERSEPSI KARAKTERISTIK INOVASI : ADOPSI E-LEARNING DI SMK YAPPI GUNUNGKIDUL - , Cahyaningsih, Nurul Indarti, Sivilokonom. Cand. Merc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to 1) identify patterns of utilization of e-learning (resources, prior to the introduction of e-learning in SMK YAPPI Gunungkidul, begin to recognize e-learning in SMK YAPPI Gunungkidul, started using e-learning in SMK YAPPI Gunungkidul, the frequency of use of e- learning, the duration of use of e-learning and course material relationship with the elearning) in SMK YAPPI Gunungkidul, 2) identify the perceptions of SMK YAPPI Gunungkidul to the use of e-learning by eight component characteristics of IT innovation adoption. The samples in this study were teachers of SMK Gunung YAPPI consisting of 30 teachers. Sampling using purposive sampling. Methods of data collection by surveys and interviews. Data analysis techniques with a descriptive analysis. Based on data analysis and the discussion concluded that: 1) The pattern of utilization of elearning in SMK YAPPI is a source of information on the use of e-learning in SMK YAPPI Gunungkidul mostly from other teachers, most teachers have never heard of e-learning in addition to e-learning SMK YAPPI in Gunungkidul, most teachers begin to recognize and use of e-learning in vocational YAPPI Gunungkidul in 2006 through 2010, the frequency of use of elearning in SMK YAPPI Gunungkidul between active teachers use (often 40% and the frequency is always 10% ) with teachers who are less active use (frequency rare 20% and sometimes 30%) is almost the same, the duration of use of e-learning at the most between 1 hour to less than 2 hours, and most of the teachers consider the relationship of e-learning in SMK YAPPI Gunungkidul to the subject matter of teaching is high, 2) perceptions of teacher characteristics on the adoption of e-learning in SMK YAPPI Gunungkidul overall height is 3.76. Component characteristic perception is the highest innovation relative advantage is 4.19. Components of perceived characteristics of innovation e-learning the lowest is the image that is 3.55.